2020
DOI: 10.3390/nu12030717
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Medical Nutrition Therapy: Parenteral Nutrition

Abstract: Parenteral nutrition has evolved tremendously, with parenteral formulas now safer and more accessible than ever. "All-in-one" admixtures are now available, which simplify parenteral nutrition usage and decrease line infection rates alongside other methods of infectious control. Recently published data on the benefits of parenteral nutrition versus enteral nutrition together with the widespread use of indirect calorimetry solve many safety issues that have emerged over the years. All these advances, alongside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…Furthermore, although the effects of EN and PN on gut microbiota are not fully understood, 13 EN demonstrates a benefit to the microbiome compared with PN in animating a diverse microbiome and preventing pathological transformations 13,14 . Nevertheless, there is an overwhelming evidence supporting the safety and effectiveness of PN in providing nutrition therapy for a range of indications in distinct groups including patients who are critically ill, patients who were not critically ill but hospitalized, and home PN recipients 4,15–17 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although the effects of EN and PN on gut microbiota are not fully understood, 13 EN demonstrates a benefit to the microbiome compared with PN in animating a diverse microbiome and preventing pathological transformations 13,14 . Nevertheless, there is an overwhelming evidence supporting the safety and effectiveness of PN in providing nutrition therapy for a range of indications in distinct groups including patients who are critically ill, patients who were not critically ill but hospitalized, and home PN recipients 4,15–17 …”
Section: Introductionmentioning
confidence: 99%
“…Enteral nutrition plays an important role in the recovery of inflammatory bowel disease and is often the first choice of nutritional therapy because it is non-invasive and can help to restore intestinal function (Luo J. et al, 2022). However, parenteral nutrition becomes the first choice when radiation enteritis is accompanied by intestinal obstruction or when fasting is required before surgery (Hellerman Itzhaki and Singer, 2020). Regardless of parenteral nutrition or enteral nutrition, the addition of certain nutrients to the nutrient solution may contribute to the recovery of the condition, for example, Glutamine can provide essential nutrition for the intestine, prevent intestinal mucosal atrophy and ameliorate intestinal immune function (Scolapio et al, 2002).…”
Section: Symptomatic Treatment Of Radiation Enteritismentioning
confidence: 99%
“…The underlying mechanism could be attributed to GLP-2’s anti-apoptotic action along with its regenerative impact on Paneth cells and intestine stem cells [ 136 ]. While parenteral nutrition remains the life-saving standard for nutrient delivery in patients with intestinal failure, serious complications may develop such as liver and intestinal mucosal barrier injury, inflammation, and bacterial translocation [ 137 , 138 ]. To further understand the role of GLP-2 to ameliorate parenteral nutrition-associated gut injury, using a mouse model of parenteral nutrition, Deng et al, showed that GLP-2 significantly suppressed the expression of pro-inflammatory cytokines TNF-a and IL-6 in the ileum and reduced serum levels of D-lactic acids and LPS [ 132 ].…”
Section: Glp-1 and Glp-2 As Regulators Of Intestine Integrity And Inf...mentioning
confidence: 99%